DEVELOPMENT AND EFFECTIVENESS OF GEOGEBRA BASED LEARNING MEDIA REVIEWED FROM LEARNING RESULT AND SELF CONFIDENT - Soffi Widyanesti Priwantoro; Syariful Fahmi (At-Taqaddum, 2019)
This study aims to develop Geogebra-based learning media in linear programing course for semester V students of Mathematics Education, Ahmad Dahlan University. The effectivenss of this learning media is measured based on student learning outcomes and confidence. The development model used is the borg and Gall development model that includes: (1) standard content analysis, (2) multimedia reference collection, (3) multimedia design, and (4) manufacture of GeoGebra-based learning media in the form of applets. The revision of learning media assessed by the material and learning experts, media experts and tested on the students, both small and large classes, I,e 38 students of mathematics education university Ahmad Dahlan. Learning media generated have good quality (B) according to the assessment of material and learning experts, media experts, and 38 students, with an average score of 209.48 from a maximum score of 260. The effectiveness of instructional media viewed from two aspects: student confidence and results learn. Geogebra-based learning media is effective regarding student self-confidence and student learning outcomes in linear course.